Microstructure Alterations of Ti-6Al-4V ELI during Turning by Using Tungsten Carbide Inserts under Dry Cutting Condition - Ibrahim, G. A.; Arinal, H.; . Zulhanif; Haron, C.H.C. (International Conference on Engineering and Technology Development (ICETD), 2012)
Titanium alloys possesses a hexagonal close packed (h.c.p) structure, called phase to ambient temperature. This structure changes to body center cubic (b.c.c), called phase to the temperature of 882 C. Machining process that generates high temperature during machining can affect on microstructures of machined surface, which represents as a quality of components. The turning parameters evaluated are cutting speed (55 - 95 m/min), feed rate (0.15 - 0.35 mm/rev), depth of cut (0.10 - 0.20 mm) and tool grade (uncoated, CVD and PVD). The aims of this paper are to investigate the effects of machining process on microstructures of machined surface and chip were machined using tungsten carbide inserts under dry cutting condition. The results show that machining at high cutting speed (95 m/min) affected on the microstructure significantly at the end of machining. The temperature is the most significant factor affected on microstructure of the machined surface and chip at shear zone. The changes of microstructure were also affected by the tool pressure during cutting.